Analisis Anthropomorphism Dalam Desain Karakter Arknights - Ika Resmika Andelina (ULTIMART Jurnal Komunikasi Visual, 2021)
Tower defense is one of the most popular genres in the game world. Arknights is one such example, but apart from the genre, one of the factors that influence Arknights' popularity is its unique character designs. Designed in the style of moe anthropomorphism, Arknights creates design variations with exciting new fictional races. Character is one of the main elements in the game that is important to build relationships with users. By using Mounsey's holistic character design and matrix manga, Arknights' anthropomorphic character design, this study finds that character abilities are the most important element that makes a character likable, then followed by an attractive character visual design in accordance with the character's abilities. Keywords: anthropomorphism; character design; game; arknights.